Strategies to alter the natural history of childhood asthma. Issue 2 (April 2017) - Lee-Sarwar, K.A.; Bacharier, L.B.; Litonjua, A.A.
Abstract : Purpose of review: Asthma exhibits significant heterogeneity in occurrence and severity over the lifespan. Our goal is to discuss recent evidence regarding determinants of the natural history of asthma during childhood, and review the rationale behind and status of major efforts to alter its course. Recent findings: Variations in microbial exposures are associated with risk of allergic disease, and the use of bacterial lysates may be a promising preventive strategy. Exposure to air pollution appears to be particularly damaging in prenatal and early life, and interventions to reduce pollution are feasible and result in clinical benefit. E-cigarette use may have a role in harm reduction for conventional cigarette smokers with asthma, but has undefined short-term and long-term effects that must be clarified. Vitamin D insufficiency over the first several years of life is associated with risk of asthma, and vitamin D supplementation reduces the risk of severe exacerbations. Summary: The identification of risk factors for asthma occurrence, persistence and severity will continue to guide efforts to alter the natural history of the disease. We have reviewed several promising strategies that are currently under investigation. Vitamin D supplementation and air pollution reduction have been shown to be effective strategies and warrant increased investigation and implementation.